Keseimbangan Tenaga Kerja pada Stasiun Kerja Bagian Proses Retouching saat Pandemi Covid-19 Dengan Pendekatan Waktu Standar - Haslindah, Andi; Hanafie, Ahmad (Patria Artha Technological Journal, 2021)
Manpower management includes the activities of determining the need for manpower both in terms of quality and quantity, finding sources of manpower effectively and efficiently. The second is labor maintenance which includes economic and non-economic programs, which are expected to provide peace of mind for workers. The aim of the research is to balance the number of workers at each work station during the Covid-19 pandemic.  The method is collecting primary data by direct survey, followed by time analysis and then balancing the number of workers based on standard time. The results obtained were able to balance the workforce that had been used before the Covid-19 pandemic from 21 workers used for 24 days of research with an average working hour of 420 minutes, raw materials used 3,865 kg per day to 13 workers with a time standard 293.5 minutes.